2017
DOI: 10.1038/s41598-017-12037-8
|View full text |Cite
|
Sign up to set email alerts
|

SOX9 Regulates Cancer Stem-Like Properties and Metastatic Potential of Single-Walled Carbon Nanotube-Exposed Cells

Abstract: Engineered nanomaterials hold great promise for the future development of innovative products but their adverse health effects are a major concern. Recent studies have indicated that certain nanomaterials, including carbon nanotubes (CNTs), may be carcinogenic. However, the underlying mechanisms behind their potential malignant properties remain unclear. In this study, we linked SOX9, a stem cell associated transcription factor, to the neoplastic-like properties of human lung epithelial cells chronically expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…SOX9 gene has been implicated in different types of cancer as an oncogene; however, it also may behave as a tumor suppressor [5, 6]. Recent findings have shown that ectoderm- and endoderm-derived tissues continue to express SOX9 in stem cell pools [7] and evidence also suggests that it may regulate CSCs [810]. However, detailed mechanisms need to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…SOX9 gene has been implicated in different types of cancer as an oncogene; however, it also may behave as a tumor suppressor [5, 6]. Recent findings have shown that ectoderm- and endoderm-derived tissues continue to express SOX9 in stem cell pools [7] and evidence also suggests that it may regulate CSCs [810]. However, detailed mechanisms need to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that JQ1 negatively affected several transcription factors known to be involved in the initiation and maintenance of the stemness phenotype in TNBC, such as MYC, EZH2, SOX9 and RUNX2 [35][36][37]. MYC, EZH2 and SOX9 are known to be repressed in response to BET inhibition in several malignancies, such as medulloblastoma, bladder cancer and myelofibrosis [14,[38][39][40], but as yet the effect of JQ1 on these genes in TNBC has not been explored. Moreover, we found that RUNX2, a stemness marker highly expressed in TNBC [41] and known to play a crucial role in breast cancer metastasis [42], can be negatively targeted by BETi in TNBC.…”
Section: Discussionmentioning
confidence: 93%
“…Sex determining region Y-box 9 (Sox9) was originally known for its functions in embryonic development specifically in bone formation, testis and lung development [42]. Sox9 is important for stem cell maintenance, tumor progression and metastasis [43]. Pluripotent Sox9 positive lung stem cells are capable of generating airway and type II cells in mice and transplantation of the Sox9+ human lung stem cells in cancer patients have been described [22,25].…”
Section: Resultsmentioning
confidence: 99%